Expert Network Time Protocol An Experience in Time with NTP - Rybaczyk, Peter (Apress : Imprint: Apress, 2005)
Have you ever tried to figure out why your computer clock is off, or why your emails somehow have the wrong timestamp? Most likely, it's due to an incorrect network time synchronization, which can be reset using the Network Time Protocol. Until now, most network administrators have been too paranoid to work with this, afraid that they would make the problem even worse. However, Expert Network Time Protocol: An Experience in Time with NTP takes the mystery out of time, and shows the network administrator how to regain the upper hand. This book is a fascinating look into NTP, and the stories behind the science. Written by Peter Rybaczyk, one of the foremost experts on NTP, this book will show the network administrator how to become more comfortable working with time.